Safety management practices and safety behavior among assistant medical officer in Kelantan Public Hospital - Muhammad Naim, Sulaiman (2020)
The present study investigated the relationship between safety management practices and safety behavior of assistant medical officer (AMO) in Kelantan public hospitals. The component of safety management practices are management commitment, safety training, safety communication and feedback, employees involvement, safety rules and procedures and safety promotion policies, while safety behavior component are safety compliance and safety participation. The questionnaire was consisted of 47 items adapted from the previous studies. The questionnaire was distributed to 250 AMOs in Kelantan public hospital for data collection and with 205 feedback, data were analyzed using SPSS version 26.0. The findings showed that management commitment, workers involvement and safety rules and procedure positively and significantly affected safety behavior where as safety training, safety communication and feedback, and safety promotion policies does not significantly influencing safety behavior. Finally, implications are discussed and recommendations for future researchers.